Association of Bevacizumab-induced Hypertension and Progression Free Survival in Patients with Breast Cancer. (June 2015) - Takahashi, Koichi; Tanaka, Hiroaki; Yamaguchi, Kazunori; Asakura, Masato; Motoki, Takahiro; Watanabe, Masahiro; Yamamoto, Takaaki; Kosaka, Shinji; Houchi, Hitoshi
Abstract : Background: Bevacizumab(Bev), an inhibitor of vascular endothelial growth factor (VEGF), is used in combination with paclitaxel (Pac)for the treatment of inoperable, advanced, or recurrent breast cancer (Pac on days 1, 8, and 15, Bev on days 1 and 15, of a 28 daycycle). Hypertension is a known side effect associated with Bev, with its incidence being 17.9% in Japan. Objective: We investigated an association between Bev-induced hypertension andprogression free survival. Method: We retrospectively studied 13 patients who received Bev for the treatment of advanced breast cancer. Weused a multiple regression analysis, in which the number of cycles were used as dependent variables and age and use or no use of antihypertensive agents were used as explanatory variables. A Mann–Whitney test was used to compare the number of cycles among antihypertensive therapy group and non-antihypertensive therapy group. Result and discussion: Multiple regression analysis showed no significant association between the number of cycles of Bev therapy and age, while a significant association between the number of cycles of Bev therapy and the use of antihypertensive agents was detected ( p < 0.01). The results also show a weak correlation between age and use of antihypertensive agents( r = 0.14). In the comparison of the number of cycles of Bev between patients in the antihypertensivetherapygroup and those in the non-antihypertensive therapy group, a significant between-group difference was found ( p < 0.01). Therefore a side effect hypertension can be a positive predictive factor for the effect of Bev therapy.